Thoracic vertebral body erosion due to a perianeurysmal outpouching lesion after thoracic endovascular aortic repair: a case report and literature review - Hong Jin Kim; Joonghyun Ahn; Kee-Yong Ha; Dong-Gune Chang (BMC Musculoskeletal Disorders)
Abstract Background The safety of endovascular treatment, such as thoracic endovascular aortic repair (TEVAR), for a descending thoracic aortic aneurysm has been well-established, with a reported low postoperative mortality rate but higher incidences of long-term complications such as endo-leakage, device failure, and aneurysm-related death. Based on this, we report the first case of massive thoracic vertebral body erosion due to a perianeurysmal outpouching lesion after TEVAR. Case presentation A 77-year-old female with a history of TEVAR due to descending thoracic aortic arch aneurysm 4 years ago was referred from the cardiovascular clinic to the spine center. The patient presented with persisting back pain, which began 3 years after TEVAR and progressively worsened. Physical examination was notable for tenderness in the upper thoracic region without any neurological deficits. Computed tomography of the aorta and thoracic spine showed bony erosion into the T5–T7 vertebral bodies. Magnetic resonance imaging of the thoracic spine confirmed a perianeurysmal outpouching lesion eroding into the T5–T7 vertebral bodies due to pulsating pressure. We performed the posterior instrumented fusion from T3 to T9 at the thoracic spine and TEVAR at remnant endo-leakage lesions. Conclusions Since the progression of such a condition can have a catastrophic outcome, and because the treatment options vary, serial follow-up through an interdisciplinary approach is important in cases with a high index of suspicion of a perianeurysmal outpouching lesion.